The Effect of Motivation and Work Discipline on Employee Performance at Rengganis Restaurant, Bandar Lampung City in 2023 - Ayu Kartika; Hepiana Patmarina (Cita konsultindo, 2024)
The research addresses the issue of inadequate employee discipline, as evidenced by absenteeism from 2019 to 2023. The objective of this study is to assess the impact of motivation and work discipline on employee performance. Employing a quantitative approach, the research involves the participation of employees from Rengganis Restaurant. The entire population, consisting of 64 individuals, serves as the respondents for this study. Data collection is conducted through interviews, observations, and questionnaires, with the application of a regression analysis formula to test hypotheses. A Likert scale questionnaire is employed, and the data is processed using the SPSS 29 program. The findings reveal that, individually, motivation does not influence employee performance significantly, whereas work discipline has a considerable impact on employee performance. Furthermore, both motivation and work discipline collectively play a role in influencing employee performance.